AUDITOR DAN TINGKAT MATERIALITAS - Aulia, Hilda Rizki; Handoyo, Sigit (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2015)
One of the phases of audit to auditor is determining the level of materiality.It is very important and must be done by auditors since the level of materiality hastight relationship both the level of risk and the obtaining of evidence. There are somefactors may infl uence in determining of the materiality level. This research will test theinfl uence of professionalism, experiences and the knowledge of auditor to detech fraudin determining of materiality level. Auditors work at accounting fi rm in Yogyakartaand Solo are the subjects and respondents of this research. Hypothesis testing is usingmultiple regression with SPSS for windows version 16.0 as a tool. The result provesthat the determining of materiality level by auditor is signifi cantly infl uenced byprofessionalism, experiences and the knowledge of auditor to detect fraud